The influence of hydrated lime on moisture susceptibility of asphalt mixtures - Zaidi, Syed Bilal Ahmed (2018)
Moisture damage is one of the major causes of premature failure of road pavements especially the pavements made using the flexible design concept. This failure occurs as a result of cohesion and adhesion loss between the binder and binder-aggregate interfaces respectively. One of the many ways of mitigating moisture damage effect is the use of anti-stripping agents like liquid polymers, Portland cement, hydrated lime, fly ash, flue dust, etc. Hydrated lime has been found to be one of the most efficient anti-stripping agents among all common additives to asphalt mixtures. Although the majority of research on the use of hydrated lime in asphalt mixtures has been carried out in the USA, the beneficial effects of hydrated lime have also been reported worldwide especially in Europe. In the UK, the use of hydrated lime only started in the early 2000’s and still needs a lot of research in terms of selection of aggregates which can be improved with the use of hydrated lime. Most of the aggregates used in the UK for asphalt mixtures are of good field performance and it is difficult to find aggregates with poor quality. That is the reason why for this research four aggregate types which are commonly used in the UK for flexible road payments are selected. One type of bitumen having penetration grade of 40/60 has been selected for the research. The four aggregate types include granite, limestone, basalt and greywacke. This research focuses on an in-depth investigation of hydrated lime performance against moisture damage in bitumen mastics and asphalts mixtures as a whole. The full project has been broken down into three parts. The first part is a component level study, the second is mixture level study and the third is the study of practical adhesion. In the component level study, the effect of hydrated lime is quantified in terms of adhesion properties between a range of aggregates and binder combinations. For the component level testing, the effect of hydrated lime is quantified by adding it to the bitumen to make a mastic. The test techniques which are used for the component level assessment includes rolling bottle test and surface energy measurement. The second part focuses on the performance of hydrated lime as a whole inside asphalt mixture as filler replacement. The idea behind this methodology is to evaluate the real effect of hydrated lime in the mixture because if hydrated lime is used as additional filler in the mixture it will alter the mixture volumetric rather than simply affecting the mechanical response of the mixture through the properties of the hydrated lime. SATS test has been used to quantify the effect of hydrated lime against moisture damage at mixture level. The third part of the research deals with the measurement of practical adhesion with and without moisture conditioning with the help of pull-off and peel-off test techniques called PATTI and Peel test. The effect of hydrated lime either in the mastic or in the mixture has been found to be aggregate type dependent. Granite aggregates showed a good improvement in the performance against moisture damage resistance with the use of hydrated lime. Limestone aggregate didn’t respond to the addition of hydrated lime in the light of most of the techniques considered in this research and the same applied to the basalt aggregates. Greywacke, on the other hand, responded well and showed an improved moisture damage performance with the use of hydrated lime. Another good thing observed in the results was the consistency between the results among the different test techniques. The results obtained in each technique are in line with each other and give the same conclusion for most of the combinations studied in this research. To conclude, the effect of hydrated lime highly depends on the type of aggregate, its origin and its mineral composition. The aggregates used in this study were either of moderate or good field performance. Although a good improvement in the moisture damage performance of some combinations was clearly observed, it is highly recommended to incorporate the aggregates having bad field performance to see how hydrated lime improves their performance.